Conclusions - Jahn Kassim, Puteri Shireen; Mohd Nawawi, Norwina; Ibrahim, Mansor (Palgrave Macmillan, 2018)
Conclusion chapter for book Modernity, nation and urban-architectural form the dynamics and Dialectics of National Identity vs Regionalism in a Tropical City